Creation of Practical and Functional Program Learning Outcomes (PLOs): A Mongolian Perspective - Yondon Altangerel , Khaliun Myagmarjav , Tungalagtuya Myagmarjav , Narantuya Dorj (South Eastern European Journal of Public Health, 2025)
Program learning outcomes define skills and abilities acquired by the student and reflect the requirements and demands of the labor market. Despite the importance of program learning outcomes, little research has been done on foreign language education bachelor's degree programs in Mongolia. This article aims to identify what the common requirements for the development of program learning outcomes are, whether the foreign language program that is currently implemented at the University of Finance and Economics in Mongolia meet these requirements, and to find out the perspectives and levels of key stakeholders' engagement in the design and implementation of learning outcomes. Different concepts and theories are applied to find out the learning outcomes’ requirements, and surveys were conducted on teachers, administrators, and employers. Based on the findings from an analysis of the foreign language education program along with the survey results of key stakeholders, current PLOs are partially designed and developed in accordance with the requirements. It was observed that key stakeholders were not considered nor played essential roles in the development and design of learning outcomes. More engagement with these stakeholders is necessary in the form of regular consultation and feedback to ensure continuous improvement that reflects key stakeholders' needs and demands being reflected in the PLOs. Based on the results of the study, it is proposed revised PLOs for foreign language education programs.